Representations of linear groups over Ā₂-algebras - Timoshin, A.S. (Algebra and Discrete Mathematics, 2004)
In the space of irreducible unitary representations
of a linear group over an algebra of type Ā₂ an open dense subset
of representations in the general position is singled out. This set is
identified, up to simple direct factors, with the space of representations of a full linear group.